Perception and expectation of journalism education in Malaysia: what’s in it for industry 4.0? - Ismail, Rizalawati; Ismail, Awan; Kasim, Azahar; Yusof, Norhafezah; Aripin, Norizah; Ishak, Mohd Sobhi (2018)
Journalism education in Malaysia is in a state of perplexity especially with the new communication technologies at hand. This paper shares the perception and expectation of some prominent media practitioners in Malaysia on journalism education. Interviews were conducted in 2017 with 15 senior news editors and chief editors of various media organisations in Malaysia. Findings on their perception and expectation were then threaded with the current trend of the fourth industrial revolution or the so-called Industry 4.0. In other words, this paper discusses the perception and expectation of the media practitioners on how journalism education in Malaysia can fulfil the needs of Industry 4.0.